OGRDB: a reference database of inferred immune receptor genes. Issue Volume 48:Issue D1(2020) (30th September 2019) - Lees, William; Busse, Christian E; Corcoran, Martin; Ohlin, Mats; Scheepers, Cathrine; Matsen, Frederick A; Yaari, Gur; Watson, Corey T; Collins, Andrew; Shepherd, Adrian J
Abstract: High-throughput sequencing of the adaptive immune receptor repertoire (AIRR-seq) is providing unprecedented insights into the immune response to disease and into the development of immune disorders. The accurate interpretation of AIRR-seq data depends on the existence of comprehensive germline gene reference sets. Current sets are known to be incomplete and unrepresentative of the degree of polymorphism and diversity in human and animal populations. A key issue is the complexity of the genomic regions in which they lie, which, because of the presence of multiple repeats, insertions and deletions, have not proved tractable with short-read whole genome sequencing. Recently, tools and methods for inferring such gene sequences from AIRR-seq datasets have become available, and a community approach has been developed for the expert review and publication of such inferences. Here, we present OGRDB, the Open Germline Receptor Database (https://ogrdb.airr-community.org ), a public resource for the submission, review and publication of previously unknown receptor germline sequences together with supporting evidence.